Haemangiopericytic meningioma of the sacral canal: a case report. Issue 2 (February 1988) - Bridges, L R; Roche, S; Nashef, L; Rose, F C
Abstract : A case of haemangiopericytic meningioma of the sacral canal in a 25 year old man, an uncommon tumour at a rare site, is described. The tumour was malignant and largely undifferentiated although there was light and electron microscopic evidence of dual differentiation in areas towards haemangiopericytoma and meningioma. The patient, with cauda equina syndrome, was treated by partial resection and post-operative radiotherapy and remains well 12 months after treatment.